A New Contact Lens Sensor System for Continuous Intraocular Pressure Monitoring: Evaluation of Safety and Tolerability. Issue 10 (12th October 2022) - Zhang, Yuning; Wei, Yifan; Karunaratne, I. K.; Lee, Ching Hymn Christopher; Deng, Mingjie; Chen, Zidong; Yang, Yangfan; Chong, Iok Tong; Lam, David C. C.; Yu, Minbin
Abstract : Purpose: To assess the safety and tolerability of a new contact lens sensor (CLS) system for continuous 3- and 24-hr intraocular pressure (IOP) monitoring in human eyes. Methods: Twenty-five subjects were recruited for 3-hr IOP measurement by CLS. Corneal fluorescein staining (CFS) scores were evaluated before and after measurement. Then, 30 participants (10 normal subjects and 20 glaucoma patients) were recruited for 24-hr IOP monitoring. Ocular surface disease index (OSDI) was assessed before and one day after measurement. Contact lens dry eye questionnaire-8 was assessed immediately after measurement. Visual analog scale of discomfort was measured before, immediately after, and one day after measurement. Best-corrected visual acuity (BCVA), tear break-up time (TBUT), and CFS were assessed before, immediately after, and 1 day after measurement. Results: All participants completed 3- or 24-hr IOP measurement by CLS. Corneal fluorescein staining increased from 0.6±0.7 to 2.4±1.5 after 3-hr IOP measurement ( P <0.001). For participants undergoing 24-hr IOP monitoring, OSDI increased from 9.1±9.7 to 18.0±12.4 ( P =0.001). CLDEQ-8 score was 11.6±5.8. Visual analog scale increased from 11.1±14.2 to 35.2±21.8 after measurement ( P <0.001) and decreased to 26.7±18.4 one day later ( P <0.001 compared with baseline). BCVA decreased from 1.0±0.01 to 0.8±0.1 ( P <0.001) and returned to 0.9±0.1 after one day ( P <0.001 compared with baseline). TBUT decreased from 5.1±3.9 to 2.6±1.5 s ( P =0.001) and returned to 4.8±2.5 s ( P =0.465 compared with baseline). Corneal fluorescein staining increased from 0.7±0.9 to 4.3±0.8 ( P <0.001) and dropped to 0.8±0.7 ( P =0.599 compared with baseline). No significant difference was found for all variations of indicators between normal subjects and glaucoma patients ( P >0.1 for all comparisons). Conclusions: The CLS shows a great potential for a safe and tolerable 24-hr IOP monitoring in normal subjects and glaucoma patients. Clinical attention to the worsening signs and symptoms after measurement is required.